ON b-ORTHOGONALITY IN 2-NORMED SPACES - S. M. Gozali; Hendra Gunawan (IndoMS, 2010)
In this note we discuss the concept of b-orthogonality in 2-normedspaces. We observe in particular that this denition of orthogonality is too loose sothat every two linearly independent vectors are b-orthogonal.DOI : http://dx.doi.org/10.22342/jims.16.2.36.127-132